2019
DOI: 10.1111/acer.14139
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Parental Alcohol Use Rather Than Parental Drinking Shapes Offspring's Alcohol Expectancies

Abstract: Background: Alcohol expectancies (AE), that is, the anticipated effects of alcohol, start developing early in childhood and are important predictors of alcohol use years later. Whereas previous research has demonstrated that parental drinking relates to children's AE, this study aims to test whether exposure to parental alcohol use mediates the link between parental alcohol use and positive and negative AE among children (6 to 8 years) and early adolescents (12 to 15 years).Methods: Longitudinal multi-informan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 47 publications
(95 reference statements)
5
29
1
1
Order By: Relevance
“…While these studies test the effects of parent drinking on expectancies, only one recent study has attempted to look at mechanisms of this association. Smit and colleagues () found that more exposure to paternal alcohol use (e.g., observing alcohol use at a family party, at dinner) mediated the effect of father drinking on childhood alcohol expectancies (Smit et al, ), predicting fewer negative expectancies among boys and greater positive expectancies among girls. However, when assessing the same question in adolescents, Smit and colleagues () found that exposure to paternal drinking mediated the effect of paternal drinking on a variety of positive but not negative alcohol expectancies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While these studies test the effects of parent drinking on expectancies, only one recent study has attempted to look at mechanisms of this association. Smit and colleagues () found that more exposure to paternal alcohol use (e.g., observing alcohol use at a family party, at dinner) mediated the effect of father drinking on childhood alcohol expectancies (Smit et al, ), predicting fewer negative expectancies among boys and greater positive expectancies among girls. However, when assessing the same question in adolescents, Smit and colleagues () found that exposure to paternal drinking mediated the effect of paternal drinking on a variety of positive but not negative alcohol expectancies.…”
mentioning
confidence: 99%
“…Smit and colleagues () found that more exposure to paternal alcohol use (e.g., observing alcohol use at a family party, at dinner) mediated the effect of father drinking on childhood alcohol expectancies (Smit et al, ), predicting fewer negative expectancies among boys and greater positive expectancies among girls. However, when assessing the same question in adolescents, Smit and colleagues () found that exposure to paternal drinking mediated the effect of paternal drinking on a variety of positive but not negative alcohol expectancies. Taken together, these findings suggest that exposure to parent alcohol use may be more important in predicting negative expectancies in childhood but positive expectancies in adolescence, when drinking initiates.…”
mentioning
confidence: 99%
“…Indeed, Dutch adolescents aged 12-14 years receive 15-20 euros (which equals an amount of 16.5-22 US dollars) per month from their parents, and their budget increases with age as they may also generate income by means of a holiday or secondary job [41]. In future research, it would be worthwhile to further explore how adolescents' food purchasing behavior in the school food environment may increase with age, linking current data with future waves of the longitudinal lifestyle cohort study [31,32]. This also holds for potential differences between boys and girls, and those with a lower versus higher educational background, as these were also found to be associated with adolescents' food purchases in the school food environment.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to recruit a nationwide representative sample of 10-to-13-year-olds and their mothers. Therefore, random sampling methods were used to recruit participants from five randomly selected regions and provinces in the Netherlands [31,32]. The regions were based on the four cardinal points (i.e., North, East, South, West).…”
Section: Procedures and Materialsmentioning
confidence: 99%
See 1 more Smart Citation